Ketahanan pangan keluarga dan kualitas konsumsi pangan sebagai faktor penentu kejadian stunting pada balita - Khasana, Tri Mei; Nareswara, Angelina Swaninda; Fitriyah, Mawaddah (Jurnal Gizi Klinik Indonesia, 2025)
Household food security and children's dietary quality as determinants of stuntingBackground: Nutritional status is determined by dietary intake, which reflects the dietary quality. Poor dietary quality directly contributes to dietary problems in toddlers and is strongly associated with household food security.Objective: This study aims to determine the correlation of family food security and dietary quality with stunting among toddlers.Methods: A cross-sectional study involving 104 toddlers aged 2-5 years who reside in the working area of Pleret Community Health Center, Bantul. Family food security was measured using the United States Household Food Security Survey Module (US-HFSSM) questionnaire. Diet quality scores were assessed using a three-level Balanced Nutrition Index (IGS3-60) based on the type of food and portions adjusted to the portions for toddlers according to the Balanced Nutrition Guidelines (PGS). Data analysis used the Chi-Square test.Results: More than half of toddlers (51%) live in food-insecure households. According to the IGS3-60, most toddlers (93.3%) show poor dietary quality. The average daily portion sizes and IGS3-60 scores for all food components are below the recommended standards of the PGS, except for animal protein, which meets the standard of three portions per day with an IGS3-60 score of 8.3 ± 3.0. Vegetables were the least consumed food group, as shown by both the average daily portions and IGS3-60 scores. Correlation analysis showed that milk consumption portions were the only dietary factor significantly associated with stunting, based on the height-for-age Z-score (p = 0.032).Conclusions: Household food security and children’s dietary quality were not associated with stunting. However, the daily portion of milk is associated with stunting.